Contrasting biogeochemical cycles of cobalt in the surface western Atlantic Ocean. Issue 12 (5th December 2014) - Dulaquais, Gabriel; Boye, Marie; Middag, Rob; Owens, Stephanis; Puigcorbe, Viena; Buesseler, Ken; Masqué, Pere; de Baar, Hein J. W.; Carton, Xavier
Abstract Dissolved cobalt (DCo; <0.2 µm; 14 to 93 pM) and the apparent particulate cobalt (PCo; >0.2 µm; <1 to 15 pM) were determined in the upper water column (<1000 m) of the western Atlantic Ocean along the GEOTRACES‐A02 section (64°N to 50°S). The lowest DCo concentrations, typical of a nutrient‐type distribution were observed in surface waters of the subtropical domains. Strong linear relationships between DCo and phosphate (P) as well as meridional gradients of decreasing DCo from high latitudes were characterized and both linked to the Co biological requirement. External sources such as the Amazon and the atmospheric deposition were found to contribute significantly (>10%) to the DCo stock of the mixed layer in the equatorial and north subtropical domains. Biotic and abiotic processes as well as the physical terms involved in the biogeochemical cycle of Co were defined and estimated. This allowed establishing the first global budget of DCo for the upper 100 m in the western Atlantic. The biological DCo uptake flux was the dominant sink along the section, as reflected by the overall nutrient‐type behavior of DCo. The regeneration varied widely within the different biogeochemical domains, accounting for 10% of the DCo‐uptake rate in the subarctic gyre and for up to 85% in southern subtropical domain. These findings demonstrated that the regeneration is likely the prevailing source of DCo in the surface waters of the western Atlantic, except in the subpolar domains where physically driven sources can sustain the DCo biological requirement.